Perundungan Dalam Novel Kisah Untuk Geri Karya Erisca Febriani - Nurul Faizah Eka Putri Riziqni; Zulfadhli (Persona: Kajian Bahasa dan Sastra, 2023)
Bullying is a social phenomenon that still frequently occurs in school or community settings. Bullying is also considered a public issue that receives global attention, both domestically and internationally. One example is in the world of literature, such as in the novel "Kisah untuk Geri" by Erisca Febriani, which portrays acts of bullying in a school environment. The focus of this article is to describe the act of bullying in Indonesian teenage novels, including (1) its forms, (2) factors, and (3) impacts. This research utilizes a qualitative descriptive method. The data source for this research is the novel "Kisah untuk Geri" by Erisca Febriani. The data collection technique used is reading and taking notes of the information found in the novel "Kisah untuk Geri" by Erisca Febriani. The results of this research will demonstrate the existence of bullying. Firstly, there are three forms of bullying, namely verbal bullying, non-verbal bullying, and physical bullying. The three variables that lead to bullying are individual, peer, and familial influences, in that order. Third, bullying has both psychological and physical effects, which are both negative.